From Survival to Productivity Mode: Cytokinins Allow Avoiding the Avoidance Strategy Under Stress Conditions - Avni, Avishai; Golan, Yelena; Shirron, Natali; Shamai, Yeela; Golumbic, Yaela; Danin-Poleg, Yael; Gepstein, Shimon (Frontiers in Plant Science, 2020)
Growth retardation and stress-induced premature plant senescence are accompanied by a severe yield reduction and raise a major agro-economic concern. To improve biomass and yield in agricultural crops under mild stress conditions, the survival must be changed to productivity mode. Our previous successful attempts to delay premature senescence and growth inhibition under abiotic stress conditions by autoregulation of cytokinins (CKs) levels constitute a generic technology toward the development of highly productive plants. Since this technology is based on the induction of CKs synthesis during the age-dependent senescence phase by a senescence-specific promoter (SARK), which is not necessarily regulated by abiotic stress conditions, we developed autoregulating transgenic plants expressing the IPT gene specifically under abiotic stress conditions. The Arabidopsis promoter of the stress-induced metallothionein gene (AtMT) was isolated, fused to the IPT gene and transformed into tobacco plants. The MT::IPT transgenic tobacco plants displayed comparable elevated biomass productivity and maintained growth under drought conditions. To decipher the role and the molecular mechanisms of CKs in reverting the survival transcriptional program to a sustainable plant growth program, we performed gene expression analysis of candidate stress-related genes and found unexpectedly clear downregulation in the CK-overproducing plants. We also investigated kinase activity after applying exogenous CKs to tobacco cell suspensions that were grown in salinity stress. In-gel kinase activity analysis demonstrated CK-dependent deactivation of several stress-related kinases including two of the MAPK components, SIPK and WIPK and the NtOSAK, a member of SnRK2 kinase family, a key component of the ABA signaling cascade. A comprehensive phosphoproteomics analysis of tobacco cells, treated with exogenous CKs under salinity-stress conditions indicated that >50% of the identified phosphoproteins involved in stress responses were dephosphorylated by CKs. We hypothesize that upregulation of CK levels under stress conditions desensitize stress signaling cues through deactivation of kinases that are normally activated under stress conditions. CK-dependent desensitization of environmental stimuli is suggested to attenuate various pathways of the avoidance syndrome including the characteristic growth arrest and the premature senescence while allowing normal growth and metabolic maintenance.